Islamic Banking Finance and Environmental Sustainability: Sector-Level Analysis from Indonesia - Farabi, Ahmad; Putri Kurniadi, Anggi; Dasilva, Helena; Thoha, Mahmud; Karimi, Kasman; Suhendra, Adi; Abinda Firdaus, Imansyah; Setiawan, Sigit; Asrori, Asrori; Salim, Zamroni (International Journal of Energy Economics and Policy, 2025)
This study aims to analyse the effect of sectoral financing by Islamic banking on greenhouse gas emissions (CO2 and CH4) in Indonesia, both in the short and long term. Using monthly time series data from January 2015 to December 2020, this study applies the autoregressive distributed lag (ARDL) and error correction model (ECM) approaches to capture the dynamics of sectoral relationships with emissions. Five main financing sectors are analysed, namely trade, construction, manufacturing, agriculture-forestry, and transportation-communication, with energy consumption and industrial price index as control variables. The estimation results show that financing the trade sector significantly reduces CO2 emissions, while the construction, transportation-communication, and energy consumption sectors increase CO2 emissions. No significant effect of financing on CH4 emissions was found, indicating that sharia financing is not yet directed at the methane-producing sector. The ECM model confirms that the transportation-communication sector contributes to CO2 reduction in the short term, and there is a correction mechanism for long-term equilibrium. This study provides an original contribution to the study of Islamic-based green finance by presenting a sectoral approach and the use of two emission indicators. The findings are practically relevant for designing Islamic green financing policies, as well as supporting the achievement of Indonesia’s net zero emission target. This study also underlines the importance of integrating maqāṣid al-sharī’ah values into financial sustainability policies.